Synthesis and biological evaluation of a tumor-selective degrader of PARP1. (1st September 2022) - Pu, Chunlan; Wang, Shirui; Luo, Dan; Liu, Yuanyuan; Ma, Xinyu; Zhang, Hongjia; Yu, Su; Lan, Suke; Huang, Qing; Deng, Rui; He, Xiang; Li, Rui
Graphical abstract: Herein we discovered a new PARP1 degrader LB23, which can induce PARP1 protein degradation with DC50 values of 53 nM in MDA-MB-231 cells and exhibited broad antiproliferative activities. In addition, PARP1 degradation DC50 values of LB23 to L-O2 cells is 3.2 μM, bearing nearly 60-fold tumor-selectivity. Highlights: LB23 induce PARP1 protein degradation with DC50 values of 53 nM in MDA-MB-231 cells. PARP1 degradation DC50 values of LB23 to L-O2 cells is 3.2 μM, bearing nearly 60-fold tumor-selectivity. Selectivity of PROTACs can be obtained by optimization of the composition and length of linker. Abstract: Poly (ADP-ribose) polymerase (PARP) inhibitors show potent antiproliferative activity in treatment with triple-negative breast cancer (TNBC) when combined with chemotherapeutic drugs. However, the emergence of safety issues and drug-resistance of PARP inhibitors prompt us to search for new strategies. It was proved that Proteolysis Targeting Chimeras (PROTACs) is more effective than traditional small molecule which can induce target proteins degradation rather than inhibition. In this article, based on the Olaparib derivatives and cereblon (CRBN) E3 ligase ligands, a series of PARP1 degraders, with linkers bearing different length and type were designed and synthesized. Among them, compound LB23 showed efficacious antiproliferative activity in various human cancer cells and can induce PARP1 protein degradation effectively. Moreover, LB23 showed 60-fold degradation selectivity in tumor cells with low degradation toxicity in normal cells. This study shows that the PROTAC tumor selectivity can be optimized by tuning the length and composition of the linker.